2018
DOI: 10.1590/s1677-5538.ibju.2018.0004.0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflammatory markers between brucella and non-brucella epididymo-orchitis

Abstract: Objectives:Brucellosis is a multi-system infectious disease that is associated with inflammation, which causes an increase in acute phase reactants. Hematological inflammatory markers of brucellosis include mean platelet volume (MPV), red cell distribution width (RDW), neutrophil/lymphocyte ratio (NLR), and platelet/lymphocyte ratio (PLR). In this study, we aimed to evaluate the diagnostic value of hematological inflammatory markers in Brucella epididymo-orchitis (BEO), and to investigate the utility of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In the current study, the rate of leukocytosis was determined as 54.5% and 71.1% in BEO and NBEO cases, respectively. In addition, similar to the study by Cift et al (13) we found a significantly lower mean WBC count in patients with BEO. In our study, a WBC count of <14.4 had high sensitivity and low specificity for BEO and accurately predicted the diagnosis in 48.9% of cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, the rate of leukocytosis was determined as 54.5% and 71.1% in BEO and NBEO cases, respectively. In addition, similar to the study by Cift et al (13) we found a significantly lower mean WBC count in patients with BEO. In our study, a WBC count of <14.4 had high sensitivity and low specificity for BEO and accurately predicted the diagnosis in 48.9% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…Although the literature contains studies reporting 10% to 30% rates for leukocytosis in BEO cases, some publications found that this percentage reached 70% (18,20). In their study comparing BEO and NBEO cases, Cift et al (13) noted that the mean WBC count was lower in the former whereas Aydın et al (14) found no difference between the two groups in terms of the mean WBC count. In the current study, the rate of leukocytosis was determined as 54.5% and 71.1% in BEO and NBEO cases, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…More than half a million people are diagnosed with brucellosis every year. 1 After acquiring Brucella, bacteria spread through hematogenous dissemination and affect various organs, such as the urinary, respiratory, central nervous system and cardiovascular. The spread of infection triggers common symptoms of illness, such as fever, nocturnal hyperhidrosis, weight loss, anorexia, arthralgia, and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of infection triggers common symptoms of illness, such as fever, nocturnal hyperhidrosis, weight loss, anorexia, arthralgia, and fatigue. 1,2 This zoonotic disease, which remains a major public and economic health issue in many developing countries, is endemic to the Middle East, South and Central America, the Mediterranean region, and India. 3 Based on reports Iran ranks second in the world in terms of brucellosis and its annual incidence is 98 to 130 people per 100,000 populations.…”
Section: Introductionmentioning
confidence: 99%